PENAMBAHAN KAPASITAS DATABASE DAN UPGRADING SYSTEM WEBSITE PERFORMANCE CHECK UNTUK PELAKSANAAN UJIAN PERPANJANGAN PERSONEL ACO DI PERUM LPPNPI CABANG BALIKPAPAN - Dheka Alfianto; Didi Hariyanto; Ramining Puspitaningsih (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Perum LPPNPI Balikpapan Branch is one of the airports that provides air navigation services in East Kalimantan. Aeronautical communication personnel are required to conduct a exam once a year so that the license remains active or valid. Based on the PM 1 of 2014 document concerning Civil Aviation Safety Regulation Part 69 (Civil Aviation Safety Regulation Part 69) concerning License. Training and Skills of Aviation Navigation Personnel, aeronautical communication personnel are required to take a test to test the license. Therefore, a better and optimal web-based test is needed to be more effective for participants and checkers. The development of the online web-based test includes the addition of basic memory capacity (database), the use of the concept of responsive web design (RWD), changing the display of questions from one page one view to the next mode, increasing the capacity for essay answers from 6000 letters/characters to 60,000 letters/characters and the addition of pass/fail statements in the user profile section. This study uses a Research and Development (R&D) research methodology. The result of this research is that further development of the web-based test has been carried out and also received a good response from each examinee and checker. It is hoped that in the future the Management at Perum LPPNPI Balikpapan Branch can use the online web test consistently.